PROFIL PRODUKSI KARKAS SAPI PERANAKAN LIMOUSIN JANTAN DI KOTA MALANG - Farida Kusuma Astuti; Hariadi Darmawan (Universitas Tribhuwana Tunggadewi, 2021)
This research aimed to analyze and evaluate and identify the carcass profile of male limousin crossbreed cows slaughtered at The Slaughterhouse (RPH) Malang city. Three hundred male limousin crossbred cows, which are slaughtered within four months, were selected as study material. The identification of male limousin crossbred cattle based on physical characteristics documented in the RPH antemortem document and direct visual observation on the unique characteristic of brown and blackish-brown colors, horns, and black hooves, and tail hair, and compact body shape. The variables observed in this study included slaughtered age, body weight, carcass weight, carcass percentage, carcass components percentage, and carcass quality grade. The results showed that the average age was 34.86±3.04 months, with a mean bodyweight of 532,44±62,47 kg, carcass weight 287,76±45.22 kg, and carcass percentages 54.11±6,16 % with carcass components percentage: meat 82,15±1,56 % and bone 17,85±1,56 %, as well as carcass quality grade at the choice grade, according to the USDA. The carcass production profile of male limousin crossbreed cattle in Malang city slaughterhouse is not optimal according to male limousin cows' genetic potential related to the environment's adaptation process and the feed is given. Therefore, the carcass production profile shows the male limousin crossbreed cattle carcass potential to meet the meat needs, especially for Malang consumers.